(3GSJcTGa cfhR GdEfJQfJs (3LeY GdeYdheGJ h GdHMK Ydi GdCfJQfJ (B/s - (3HQjGf cdjL (B.s; (3HQjGf cdjL (B.s ((3GdQjGV (B:s (3ecJHI LQjQ(B.,s, 2002)
(3Cf gPG GdcJGH jRjO ef egGQGJc ai GdHMK Ydi GdCfJQfJ h jHjf dc cja JVHW cdeGJ GdHMK h JYOjd GdHMK GPG de JYKQ Ydi fJGFL GdHMK CjVG GSJNOGe GdYedGA GdCdjcJQhfjjf (B.s
(3GdHMK Ydi GdCfJQfJ(B.s
Keywords: (3GdCfJQfJ (B- (3HMK(B.s